2018
DOI: 10.1136/bmjopen-2017-017689
|View full text |Cite
|
Sign up to set email alerts
|

Can obesity and physical activity predict outcomes of elective knee or hip surgery due to osteoarthritis? A meta-analysis of cohort studies

Abstract: ObjectiveThe aim of this study was to systematically review the literature to identify whether obesity or the regular practice of physical activity are predictors of clinical outcomes in patients undergoing elective hip and knee arthroplasty due to osteoarthritis.DesignSystematic review and meta-analysis.Data source and eligibility criteriaA systematic search was performed on the Medline, CINAHL, EMBASE and Web of Science electronic databases. Longitudinal cohort studies were included in the review. To be incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 85 publications
2
40
0
1
Order By: Relevance
“…showed that obese patients undergoing TKR experienced less improvement in physical function compared to non-obese patients [ 129 ]. Patients with obesity are also at higher risk of developing post-surgical complications, including deep vein thrombosis, dislocation and infection, which may compromise implant survival and outcome [ 130 ].…”
Section: Therapeutic Strategies For Obesity-related Oamentioning
confidence: 99%
“…showed that obese patients undergoing TKR experienced less improvement in physical function compared to non-obese patients [ 129 ]. Patients with obesity are also at higher risk of developing post-surgical complications, including deep vein thrombosis, dislocation and infection, which may compromise implant survival and outcome [ 130 ].…”
Section: Therapeutic Strategies For Obesity-related Oamentioning
confidence: 99%
“…The impact of obesity in lower extremity TJA, particularly total knee arthroplasty (TKA), has been widely established. This includes higher rates of post-operative complications, such as infection [10], [11], [12], all-cause revision surgery [12], and mortality [2]. Obesity is also associated with increased operative time, hospital length of stay, and readmission rates [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also associated with increased operative time, hospital length of stay, and readmission rates [13], [14]. However, when it comes to patient-reported outcome (PRO) measures, the impact of obesity becomes less clear due to conflicting reports [3], [4], [11], [15], [16] likely reflecting geographic variations, outcome measures used, research methodology, and severity of obesity (all obese patients vs morbidly obese). In addition, most previous studies have focused on TKA, leaving limited information on the effect of obesity on PROs following total hip arthroplasty (THA).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, some ISTCs achieved better outcomes than NHS facilities for elective surgery, but the differences were marginal even though they had healthier, more affluent patients 34. Moreover, outcomes were not adjusted for key influences such as BMI 35. ISTCs also provide poorer training environments,36 reduce communication across institutional boundaries,37 and, in an example where surgery was transferred from a NHS hospital to a nearby ISTC, reduce overall activity 38…”
Section: Quality Of Carementioning
confidence: 99%